Critical Discourse Analysis of Pertamina’s Press Release "Supported by the Attorney General’s Office, Pertamina Ensures Pertamax Meets Specifications" - Romadhan, Mohammad Insan; Pariyanto, Pariyanto; Suwandha, Aisyah Indha (Journal of Scientific Research, Education, and Technology (JSRET), 2025)
This study examines Pertamina’s crisis communication strategy through Critical Discourse Analysis (CDA) of its press release addressing fuel quality concerns and distribution irregularities. Using Norman Fairclough’s three-dimensional model, the research analyzes textual, discursive, and social dimensions to reveal how corporate discourse is structured to maintain institutional legitimacy. The findings indicate that Pertamina employs authoritative modality and institutional alignment with the Attorney General’s Office, Ditjen Migas, and Lemigas to reinforce public confidence in fuel quality. Additionally, the press release utilizes issue diversion strategies, shifting focus toward technical compliance, independent verification, and long-term energy transition goals. The discourse functions as a tool for public perception control, ensuring the dominant narrative supports Pertamina’s credibility. This study highlights how corporate crisis communication is not purely informative but also strategically designed to shape public discourse, emphasizing the need for critical media evaluation of corporate narratives